Baby Monkey, private eye - Selznick, Brian 1966-; Serlin, David 1951- (Scholastic Press, 2018)
Baby Monkey, private eye, will investigate stolen jewels, missing pizzas, and other mysteries...if he can manage to figure out how to put his pants on